2019
DOI: 10.21203/rs.2.16862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Practice of Counseling by Community Pharmacists in Bisha Health Directorate, Saudi Arabia – Simulated Patient Visit

Abstract: Background Many organizations have suggested a minimum standard of counseling for patients, which includes information about the name of the drug, description, indication, how to use it, the method of treatment, precautions, adverse reactions, and any contraindications. Correspondingly, the World Health Organization (WHO) has recommended spending at least 3 minutes with each patient to undertake counseling. The present study aimed to evaluate the practice of counseling by community pharmacists for both over-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The same result was observed in a simulated patient study assessing the practice of counseling by the community pharmacist in Saudi Arabia, where none of the pharmacists asked if the patients were taking any other medications. 33 In another study from Ethiopia, higher results were found as 11.7% of the pharmacists asked about current medications and 21.7% asked about medication history. 34 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The same result was observed in a simulated patient study assessing the practice of counseling by the community pharmacist in Saudi Arabia, where none of the pharmacists asked if the patients were taking any other medications. 33 In another study from Ethiopia, higher results were found as 11.7% of the pharmacists asked about current medications and 21.7% asked about medication history. 34 …”
Section: Discussionmentioning
confidence: 94%
“…Moreover, our findings were in accordance with the results from the Saudi SP study, where almost 83% of the participating pharmacists did not provide information about drug interaction. 33 Another study revealed that the knowledge of community pharmacists regarding DDIs was inadequate. Major and minor DDIs were not identified by most of the participated pharmacists.…”
Section: Discussionmentioning
confidence: 99%